2015
DOI: 10.32398/cjhp.v13i1.1810
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Undergraduate and Graduate Students in Stress and Coping Strategies

Abstract: Background and Purpose: Stress among college students, and the related health and academic consequences, remains an important issue for college health professionals. Yet, less is known about the reported coping strategies among both undergraduate and graduate students. Purpose: This crosssectional study examined differences between undergraduate and graduate college students in stress levels and coping behaviors. Methods: An online health behavior survey was administered to a random sample of 1,139 college stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
4
18
0
1
Order By: Relevance
“…Moreover, this study’s results found that anxiety and depression symptoms as well as mental health status did not differ significantly by gender, age, residential status, education level, and educational discipline. In terms of age, residential status, education level, and educational discipline, literature on college students have also found insignificant differences across these groups (Ickes et al 2015 ; Liu et al 2019 ; Saleh et al 2017 ). In terms of gender, there has been some inconsistency in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study’s results found that anxiety and depression symptoms as well as mental health status did not differ significantly by gender, age, residential status, education level, and educational discipline. In terms of age, residential status, education level, and educational discipline, literature on college students have also found insignificant differences across these groups (Ickes et al 2015 ; Liu et al 2019 ; Saleh et al 2017 ). In terms of gender, there has been some inconsistency in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…For the postgraduate students, there was little association, although the reason for this is not clear from the present data. It has been suggested that stress levels are similar between undergraduate and postgraduate students, yet postgraduate students typically have greater social support, 50 which may attenuate the potentially positive relationship between PA and attainment.…”
Section: Discussionmentioning
confidence: 99%
“…For postgraduate students there was little association, although the reason for this is not clear from the present data. It has been suggested that stress levels are similar between undergraduate and postgraduate students, yet postgraduate students typically have greater social support 50 which may attenuate the potentially positive relationship between PA and attainment.…”
Section: Discussionmentioning
confidence: 99%